Chinese factor in Central Asia (Journal of Oriental Studies, 2018)
In this paper the author investigate the Chinese factor in Central Asiancountries. Through the prism of the geopolitical situation in Central Asia,the author evaluates the relationship of China and the RK. The author alsoreviewed the internal problems of China that may have an impact on China’spolicy in Central Asia.